Research of the Optimization Design and Experimental of Gear Modification based on ROMAX - Yang Jianjun; Liu Wei; Zhang Hua; Xu Aijun (Jixie chuandong)
Taking a tractor gearbox transmission system as the research object,the deformation of transmission shaft and the dislocation of gear are analyzed based on ROMAX software. The transmission error curve and the meshing characteristic of modification gear are studied,and the optimal modification quantity is determined,and the mechanism and influencing factors of the gear vibration and noise are analyzed. After the bench test of modifying helical gear is carried out,the vibration characteristic of modification gear and unmodified gear are analyzed,and the correctness of gear modification effects is verified.